Differences in PFAS exposure between Pacific pinnipeds: The Galapagos (Zalophus wollebaeki) and California (Zalophus californianus) sea lions - Ashley E. Cave; Isabella G. Livingston; Taylor M. Gregory; Eleanor C. Hawkins; Shelly Vaden; Marjorie Riofrío-Lazo; Diane Deresienski; Gregory A. Lewbart; Anthony J. Orr; Emily Griffith; Christopher Fuller; Mark J. Strynar; et al. (Marine Pollution Bulletin, 2026)

An mTOR inhibitor discovery system using drug-sensitized yeast - Anna K. Breen; Sarah Thomas; David Beckett; Matthew Agsalud; Graham Gingras; Judd Williams; Brian M. Wasko (GeroScience, 2025)
Inhibition of the target of rapamycin (TOR/mTOR) protein kinase by the drug rapamycin extends lifespan and health span across diverse species. However, rapamycin has potential off-target and side effects that warrant the discovery of additional TOR inhibitors. TOR was initially discovered in Saccharomyces cerevisiae (yeast) which contains two TOR paralogs, TOR1 and TOR2 . Yeast lacking functional Tor1 are viable but are hypersensitive to growth inhibition by TORC1 inhibitors, which is a property of yeast that can be exploited to identify TOR inhibitors. Additionally, yeast lacking FK506-sensitive proline rotamase ( FPR1 ) or containing a tor1-1 allele (a mutation in the Fpr1-rapamycin binding domain of Tor1) are robustly and selectively resistant to rapamycin and analogs that allosterically inhibit TOR activity via an FPR1 -dependent mechanism. To facilitate the identification of TOR inhibitors, we generated a panel of yeast strains with mutations in TOR pathway genes combined with the removal of 12 additional genes involved in drug efflux. This creates a drug-sensitive strain background that can sensitively and effectively identify TOR inhibitors. In a wild-type yeast strain background, 25 µM of Torin1 and 100 µM of GSK2126458 (omipalisib) are necessary to observe TOR1 -dependent growth inhibition by these known TOR inhibitors. In contrast, 100 nM Torin1 and 500 nM GSK2126458 (omipalisib) are sufficient to identify TOR1- dependent growth inhibition in the drug-sensitized background. This represents a 200-fold and 250-fold increase in detection sensitivity for Torin1 and GSK2126458, respectively. Additionally, for the TOR inhibitor AZD8055, the drug-sensitive system resolves that the compound results in TOR1- dependent growth sensitivity at 100 µM, whereas no growth inhibition is observed in a wild-type yeast strain background. Our platform also identifies the caffeine analog aminophylline as a TOR1 -dependent growth inhibitor via selective tor1 growth sensitivity. We also tested nebivolol, isoliquiritigenin, canagliflozin, withaferin A, ganoderic acid A, and taurine and found no evidence for TOR inhibition using our yeast growth-based model. Our results demonstrate that this system is highly effective at identifying compounds that inhibit the TOR pathway. It offers a rapid, cost-efficient, and sensitive tool for drug discovery, with the potential to expedite the identification of new TOR inhibitors that could serve as geroprotective and/or anti-cancer agents.

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

The Surgical Repair of a Salter-Harris Type-2 Physeal Fracture of the Proximal Phalanx in a Foal - Louise J. Breen; Matthew O.D. Coleridge; Tom O'Brien (Journal of Equine Veterinary Science, 2023)

Empowering Black Scientists in STEM: Early Success of the Black Biomechanists Association - Erica Bell; Kayla Seymore; Sarah Breen; Matthew McCullough (Biomedical Engineering Education, 2022)

Transcriptome annotation reveals minimal immunogenetic diversity among Wyoming toads, Anaxyrus baxteri - Kara B. Carlson; Dustin J. Wcisel; Hayley D. Ackerman; Jessica Romanet; Emily F. Christiansen; Jennifer N. Niemuth; Christina Williams; Matthew Breen; Michael K. Stoskopf; Alex Dornburg; Jeffrey A. Yoder (Conservation Genetics, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genome-wide DNA copy number analysis and targeted transcriptional analysis of canine histiocytic malignancies identifies diagnostic signatures and highlights disruption of spindle assembly complex - Katherine Kennedy; Rachael Thomas; Jessica Durrant; Tao Jiang; Alison Motsinger-Reif; Matthew Breen (Chromosome Research, 2019)

Genomic profiling of canine mast cell tumors identifies DNA copy number aberrations associated with KIT mutations and high histological grade - Hiroyuki Mochizuki; Rachael Thomas; Scott Moroff; Matthew Breen (Chromosome Research, 2017)

Genome-wide assessment of recurrent genomic imbalances in canine leukemia identifies evolutionarily conserved regions for subtype differentiation - Sarah C. Roode; Daniel Rotroff; Anne C. Avery; Steven E. Suter; Dorothee Bienzle; Joshua D. Schiffman; Alison Motsinger-Reif; Matthew Breen (Chromosome Research, 2015)

Comparative cytogenetic characterization of primary canine melanocytic lesions using array CGH and fluorescence in situ hybridization - Kelsey Poorman; Luke Borst; Scott Moroff; Siddharth Roy; Philippe Labelle; Alison Motsinger-Reif; Matthew Breen (Chromosome Research, 2015)

Genomics in a changing arctic: critical questions await the molecular ecologist - Stan D. Wullschleger; Amy L. Breen; Colleen M. Iversen; Matthew S. Olson; Torgny Näsholm; Ulrika Ganeteg; Matthew D. Wallenstein; David J. Weston (Molecular Ecology, 2015)
Molecular ecology is poised to tackle a host of interesting questions in the coming years. The Arctic provides a unique and rapidly changing environment with a suite of emerging research needs that can be addressed through genetics and genomics. Here we highlight recent research on boreal and tundra ecosystems and put forth a series of questions related to plant and microbial responses to climate change that can benefit from technologies and analytical approaches contained within the molecular ecologist's toolbox. These questions include understanding (i) the mechanisms of plant acquisition and uptake of N in cold soils, (ii) how these processes are mediated by root traits, (iii) the role played by the plant microbiome in cycling C and nutrients within high‐latitude ecosystems and (iv) plant adaptation to extreme Arctic climates. We highlight how contributions can be made in these areas through studies that target model and nonmodel organisms and emphasize that the sequencing of the Populus and Salix genomes provides a valuable resource for scientific discoveries related to the plant microbiome and plant adaptation in the Arctic. Moreover, there exists an exciting role to play in model development, including incorporating genetic and evolutionary knowledge into ecosystem and Earth System Models. In this regard, the molecular ecologist provides a valuable perspective on plant genetics as a driver for community biodiversity, and how ecological and evolutionary forces govern community dynamics in a rapidly changing climate.

Application of an unmanned aerial vehicle in spatial mapping of terrestrial biology and human disturbance in the McMurdo Dry Valleys, East Antarctica - Barbara Bollard-Breen; John D. Brooks; Matthew R. L. Jones; John Robertson; Sonja Betschart; Olivier Kung; S. Craig Cary; Charles K. Lee; Stephen B. Pointing (Polar Biology, 2015)

Genomic profiling reveals extensive heterogeneity in somatic DNA copy number aberrations of canine hemangiosarcoma - Rachael Thomas; Luke Borst; Daniel Rotroff; Alison Motsinger-Reif; Kerstin Lindblad-Toh; Jaime F. Modiano; Matthew Breen (Chromosome Research, 2014)

Genetic consequences of glacial survival: the late Quaternary history of balsam poplar ( Populus balsamifera L.) in North America - Amy L. Breen; David F. Murray; Matthew S. Olson (Journal of Biogeography, 2012)
Aim Beringia, the unglaciated region encompassing the former Bering land bridge, as well as the land between the Lena and Mackenzie rivers, is recognized as an important refugium for arctic plants during the last ice age. Compelling palaeobotanical evidence also supports the presence of small populations of boreal trees within Beringia during the Last Glacial Maximum. The occurrence of balsam poplar ( Populus balsamifera ) in Beringia provides a unique opportunity to assess the implications of persistence in a refugium on present‐day genetic diversity for this boreal tree species. Location North America. Methods We sequenced three variable non‐coding regions of the chloroplast genome (cpDNA) from 40 widely distributed populations of balsam poplar across its North American range. We assessed patterns of genetic diversity, geographic structure and historical demography between glaciated and unglaciated regions of the balsam poplar’s range. We also utilized a coalescent model to test for divergence between regions. Results Levels of genetic diversity were consistently greater for populations at the southern margin (θ W = 0.00122) than in the central (θ W = 0.00086) or northern (θ W = 0.00034) regions of the current distribution of balsam poplar, and diversity decreased with increasing latitude ( R 2 = 0.49, P 0.01). We detected low, but significant, structure ( F CT = 0.05, P = 0.05), among regions of P. balsamifera ’s distribution. The cpDNA genealogy was shallow, however, showing an absence of highly differentiated chloroplast haplotypes. Coalescent analyses supported a model of divergence between the southern ice margin and the northern unglaciated region of balsam poplar’s distribution, but analyses of other regional comparisons did not converge. Main conclusions The palaeobotanical record supports the presence of a Beringian refugium for balsam poplar, but we were unable to definitively identify the presence of known refugial populations based on genetic data alone. Balsam poplar populations from Beringia are not a significant reservoir of cpDNA diversity today. Unique alleles that may have been present in the small, isolated populations that survived within Beringia were probably lost through genetic drift or swamped by post‐glacial, northward migration from populations south of the ice sheets.

Anchoring the dog to its relatives reveals new evolutionary breakpoints across 11 species of the Canidae and provides new clues for the role of B chromosomes - Shannon E. Duke Becker; Rachael Thomas; Vladimir A. Trifonov; Robert K. Wayne; Alexander S. Graphodatsky; Matthew Breen (Chromosome Research, 2011)

Germin-like proteins (GLPs) in cereal genomes: gene clustering and dynamic roles in plant defence - James Breen; Matthew Bellgard (Functional & Integrative Genomics, 2010)

Microarray-based cytogenetic profiling reveals recurrent and subtype-associated genomic copy number aberrations in feline sarcomas - Rachael Thomas; Victor E. Valli; Peter Ellis; Jerold Bell; Elinor K. Karlsson; John Cullen; Kerstin Lindblad-Toh; Cordelia F. Langford; Matthew Breen (Chromosome Research, 2009)

Extensive conservation of genomic imbalances in canine transmissible venereal tumors (CTVT) detected by microarray-based CGH analysis - Rachael Thomas; Clare Rebbeck; Armand M. Leroi; Austin Burt; Matthew Breen (Chromosome Research, 2009)

Influence of genetic background on tumor karyotypes: Evidence for breed-associated cytogenetic aberrations in canine appendicular osteosarcoma - Rachael Thomas; Huixia J. Wang; Pei-Chien Tsai; Cordelia F. Langford; Susan P. Fosmire; Cristan M. Jubala; David M. Getzy; Gary R. Cutter; Jaime F. Modiano; Matthew Breen (Chromosome Research, 2009)

Tackling the characterization of canine chromosomal breakpoints with an integrated in-situ/in-silico approach: The canine PAR and PAB - Andrea C. Young; Ewen F. Kirkness; Matthew Breen (Chromosome Research, 2008)

Evolutionarily conserved cytogenetic changes in hematological malignancies of dogs and humans – man and his best friend share more than companionship - Matthew Breen; Jaime F. Modiano (Chromosome Research, 2008)

The search for a marsupial XIC reveals a break with vertebrate synteny - Lance S. Davidow; Matthew Breen; Shannon E. Duke; Paul B. Samollow; John R. McCarrey; Jeannie T. Lee (Chromosome Research, 2007)

A high-resolution comparative map of canine Chromosome 5q14.3?q33 constructed utilizing the 1.5 canine genomesequence - KenineE. Comstock; Frode Lingaas; EwenF. Kirkness; Christophe Hitte; Rachael Thomas; Matthew Breen; Francis Galibert; ElaineA. Ostrander (Mammalian Genome, 2004)

The cnm locus, a canine homologue of human autosomal forms of centronuclear myopathy, maps to chromosome2 - Laurent Tiret; Stphane Blot; Jean-Louis Kessler; Hugues Gaillot; Matthew Breen; Jean-Jacques Panthier (Human Genetics, 2003)

Construction and integration of radiation-hybrid and cytogenetic maps of dog Chromosome X - Helen F. Spriggs; Nigel G. Holmes; Matthew Breen; Panos Deloukas; Cordelia F. Langford; Mark T. Ross; Nigel P. Carter; Maria E. Davis; Catherine Knights; Angela Smith; Christine J. Farr; Linda C. McCarthy; et al. (Mammalian Genome, 2003)

Molecular cytogenetic analysis of a novel high-grade canine T-lymphoblastic lymphoma demonstrating co-expression of CD3 and CD79a cell markers - Rachael Thomas; Ken C. Smith; Rob Gould; Sue M. Gower; Matthew M. Binns; Matthew Breen (Chromosome Research, 2001)

Canine TCOF1; cloning, chromosome assignment and genetic analysis in dogs with different head types - Kim E. Haworth; Ira Islam; Matthew Breen; Wendy Putt; Eleni Makrinou; Matthew Binns; David Hopkinson; Yvonne Edwards (Mammalian Genome, 2001)

An integrated cytogenetic, radiation-hybrid, and comparative map of dog Chromosome 5 - Rachael Thomas; Matthew Breen; Panos Deloukas; Nigel G. Holmes; Matthew M. Binns (Mammalian Genome, 2001)

Canine homolog of the T-box transcription factor T; failure of the protein to bind to its DNA target leads to a short-tail phenotype - Kim Haworth; Wendy Putt; Bruce Cattanach; Matthew Breen; Matthew Binns; Frode Lingaas; Yvonne H. Edwards (Mammalian Genome, 2001)

Mapping of 13 horse genes by fluorescence in-situ hybridization (FISH) and somatic cell hybrid analysis - Gabriella Lindgren; Matthew Breen; Sophie Godard; Ann Bowling; James Murray; Marcia Scavone; Loren Skow; Kaj Sandberg; Gérard Guérin; Matthew Binns; Hans Ellegren (Chromosome Research, 2001)

Molecular analysis and chromosomal assignment of the canine CALC-I/α-CGRP gene - Sonja Wende; Andrea Krempler; Matthew Breen; Leo Brunnberg; Bertram Brenig (Mammalian Genome, 2000)

Cloning of the canine gene encoding transcription factor Pit-1 and its exclusion as candidate gene in a canine model of pituitary dwarfism - Irma S. Lantinga-van Leeuwen; Jan A. Mol; Hans S. Kooistra; Ad Rijnberk; Matthew Breen; Corinne Renier; Bernard A. van Oost (Mammalian Genome, 2000)

Localization and Characterization of Nucleotide Sequences From the Canine Y Chromosome - Michael Olivier; Matthew Breen; Matthew M. Binns; George Lust (Chromosome Research, 1999)

The DAPI Banded Karyotype of the Domestic Dog (Canis familiaris) Generated Using Chromosome-Specific Paint Probes - Matthew Breen; Joern Bullerdiek; Cordelia F. Langford (Chromosome Research, 1999)

Chromosomal localization of acidic and basic keratin genes of the domestic dog - Amy B. Miller; Matthew Breen; Keith E. Murphy (Mammalian Genome, 1999)

Molecular characterization and chromosomal assignment of the canine protein C gene - Tosso Leeb; Thorsten Kopp; Alexandra Deppe; Matthew Breen; Ulrike Matis; Leo Brunnberg; Bertram Brenig (Mammalian Genome, 1999)

Bovine Papillomavirus Type 5: Partial Sequence and Comparison with Other Bovine Papillomaviruses - Natalie Bloch; Matthew Breen (Virus Genes, 1997)

Genetical and physical assignments of equine microsatellites—first integration of anchored markers in horse genome mapping - Matthew Breen; Gabriella Lindgren; Matthew M. Binns; Julianne Norman; Zlaka Irvin; Kevin Bell; Kaj Sandberg; Hans Ellegren (Mammalian Genome, 1997)